Análisis estadístico de la prevalencia de enfermedades oftalmológicas en caninos consultados en centros de atención veterinaria de la ciudad de Babahoyo - Jurado Arcos, Alexis Richard (2023)
The objective of this research work is to determine through surveys for an analysis of what are the ophthalmological diseases that can be found in dogs treated in veterinary care centers of the City of Babahoyo, lately people are more cautious with their pets because they are already considered members of the family so checkups are usually done for a change in the behavior of the dog, 90 surveys were conducted in different veterinary care centers taking into account data such as; race, sex, age, and type of ophthalmological pathology present obtaining as results in the breeds Mestiza 31.1%, Poodle with 14.4%, English Bulldog with 7.8%, Schnuzer with 6.7%, Pit Bull and Shih Tzu with 4.4%, French Bulldog, Boston Terrier, Neapolitan Mastiff and Pug with 3.3% among other breeds with prevalence of 1.1%. As for sex, finding in males a 60% higher prevalence than in females with 40%. The ophthalmological diseases that were found were Cataracts with 31.1%, Corneal ulcers with 20%, Prolapse of the lacrimal gland of the third eyelid with 17.8%, Conjunctivitis with 11.1%, Glaucoma with 6.7%, Keratoconjunctivitis sicca and Keratoconjunctivitis with 4.4%, Ocular enucleation with 2.2%, Anterior Uveitis and Eyelid tumors with 1.1%. All these are pathologies are very dangerous therefore they should be tended once the symptomatology is presented.